Sosialisasi Langkah Cuci Tangan Yang Benar Guna Mewujudkan Masyarakat Sehat Di Sman 2 Sibolga - Sumaiyah Sumaiyah; Marianne Marianne; Embun Suci Nasution; Dewi Pertiwi; Sony Eka Nugraha (LPPM UMRI, 2020)
Washing hands is a simple step that can be improve the level of health of oneself, family and community. World Health Organization (WHO) has provided rules regarding good and proper washing steps, whereby the Indonesian government is promoting its socialization especially in the school environment. Senior High School (SMA) Negeri 2 Sibolga is one of the randomly selected schools to carry out the right hand washing step socialization according to WHO. The level of student’s knowledge about the correct steps for washing hands has been shown increase after socialization.